Chronic hepatitis C viral infection subverts vaccine-induced T-cell immunity in humans - Kelly, C; Swadling, L; Capone, S; Brown, A; Richardson, R; Halliday, J; von Delft, A; Oo, Y; Mutimer, D; Kurioka, A; Hartnell, F; Collier, J; et al. (Wiley, 2016)
Adenoviral vectors encoding hepatitis C virus (HCV) nonstructural (NS) proteins induce multispecific, high-magnitude, durable CD4+ and CD8+ T-cell responses in healthy volunteers. We assessed the capacity of these vaccines to induce functional HCV-specific immune responses and determine T-cell cross-reactivity to endogenous virus in patients with chronic HCV infection. HCV genotype 1-infected patients were vaccinated using heterologous adenoviral vectors (ChAd3-NSmut and Ad6-NSmut) encoding HCV NS proteins in a dose escalation, prime-boost regimen, with and without concomitant pegylated interferon-α/ribavirin therapy. Analysis of immune responses ex vivo used human leukocyte antigen class I pentamers, intracellular cytokine staining, and fine mapping in interferon-γ enzyme-linked immunospot assays. Cross-reactivity of T cells with population and endogenous viral variants was determined following viral sequence analysis. Compared to healthy volunteers, the magnitude of HCV-specific T-cell responses following vaccination was markedly reduced. CD8+ HCV-specific T-cell responses were detected in 15/24 patients at the highest dose, whereas CD4+ T-cell responses were rarely detectable. Analysis of the host circulating viral sequence showed that T-cell responses were rarely elicited when there was sequence homology between vaccine immunogen and endogenous virus. In contrast, T cells were induced in the context of genetic mismatch between vaccine immunogen and endogenous virus; however, these commonly failed to recognize circulating epitope variants and had a distinct partially functional phenotype. Vaccination was well tolerated but had no significant effect on HCV viral load. Conclusion: Vaccination with potent HCV adenoviral vectored vaccines fails to restore T-cell immunity except where there is genetic mismatch between vaccine immunogen and endogenous virus; this highlights the major challenge of overcoming T-cell exhaustion in the context of persistent antigen exposure with implications for cancer and other persistent infections.